Knapsack based ECC for digital signature authentication. (4th August 2009) - Rajaram, R.; Amutha Prabakar, M.; Indra Devi, M.
Elliptic curve cryptography (ECC) provides a secure means of exchanging keys among communicating hosts using the Diffie Hellman key exchange algorithm. Encryption and decryption of texts and messages have also been attempted. This paper presents the ECC implementation for digital signature authentication and then applying the knapsack algorithm on ECC signing message. In this paper, we attempt to provide more secure digital signature scheme by using knapsack based ECC. We compare our proposed algorithm with RSA based digital signature authentication algorithm and show that our algorithm is better due to the high degree of sophistication and complexity involved. It is almost infeasible to attempt a brute force attack. Moreover, only one parameter namely the knapsack vector ai needs to be kept secret. On the contrary in RSA, three parameters such as the modulus n, its factors p and q need to be kept secret.